Synthesis and Antiinflammatory Activity of Some Novel Benzo(b)thiophene Substituted Thiazolidinones - Gouda, T. Shivaraj; Jagadish; Salahuddin, Md.; Shantakumar, S.M. (Asian Journal of Chemistry, 2010)
The 2-amino-4,5,6,7-tetrahydrobenzo(b)thiophene-3-carboxylate (I) was prepared by treating an equimolar concentration of cyclohexanone, ethylcyanoacetate, sulphur and diethylamine in dry alcohal. The compound (II) was refluxed for about 18-20 h with different aromatic aldehydes in absolute alcohol to obtain III(a-f). The obtained intermediates are treated with mercapto acetic acid to get IV(a-f). The synthesized compounds were evaluated for antiinflammatory activity. The compound IVd and IVe showed significant activity when compared to standard diclofenac sodium.